Michel Foucault: Subjectivity and Ethics of the Self as Practice of Freedom - Kebung, Konrad (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2019)
This article presents the thoughts of Michel Foucault, a cultural historian, philosopher, and intellectual, who brilliantly analyses the historical events of the past as creative criticisms for shaping human attitudes today. Through this historical analysis, Foucault examines the ways in which subjects were formed from classical times to the present. Foucault sees how this process takes a long time, starting from the subject as formed through various discourses to the subject as forming itself. To arrive at the latter, Foucault brings his readers to the classical Greco-Roman era to see how humans live their freedom and responsibilities. He also shows them various practices of the self through meditation and inner examination, as well as the practice of telling the truth (parrhesia) to oneself and to others. All this in the era was known as ethics and also seen as a practice of freedom. For Foucault, life must always be seen as a work of art that requires the attention of the artist from time to time in order to arrive at an art level considered useful and valuable to many people. Foucault calls this an aesthetic of existence, where life is not merely seen as something given, but also that must always be fought for creatively from day to day. Life must be seen as an unstable condition in which there are always cracks, therefore it has to be fixed from time to time. This is what Foucault calls a model of human existence.